First identification of Salmonella Urbana and Salmonella Ouakam in humans in Africa - Courage Kosi Setsoafia Saba; Jose Antonio Escudero; Silvia Herrera-Leon; Maria Concepcion Porrero; Monica Suarez; Lucas Dominguez; Bawa Demuyakor; Bruno Gonzalez-Zorn (Journal of Infection in Developing Countries)
Introduction: Salmonella infections are increasing worldwide, but there are few reports on Salmonella surveillance in African countries and other developing countries. This has made it difficult to estimate the actual burden of salmonellosis, especially in Africa. This study was conducted in a neglected Northern Region of Ghana where there are no previous data on Salmonella serotypes. Methodology: Standard microbiological tests were used for isolation, identification, and serotyping. Micro-dilution was used for the antimicrobial susceptibility tests. Results: Four serotypes of Salmonella were identified: S. Urbana, S. Ouakam, S. Senftenberg, and S. Stanleyville. All the serotypes were susceptible to the 20 antibiotics used in the susceptibility test. S. Urbana and S. Ouakam were identified in humans for the first time in Africa. Conclusion: This study may serve as a baseline study for future investigations on Salmonella in the region and may assist public health officials to take the appropriate measures in case of a disease outbreak caused by Salmonella in the area. The article may also give health officials a fair idea of the resistance level of these serotypes in the region.